Effect of impeller diameter to vessel diameter ratio on gas holdup - Mohd. Sobri Takriff,; W.R. Penney,; J.B. Fasano, (2000)
Numerous gas holdup correlations have been developed for predicting gas holdup in agitated vessels. However; gas holdup studies were only limited to the use of impeller diameter to vessel diameter ratio (Di/DT) of approximately 1/3. None of the available correlations considered the effect of (Di/DT) variation on gas holdup. This work was carried out to investigate this effect. The results of this investigation showed that the gas holdup increases with (Di/DT) ratio. The effect of (Di/DT) variation on gas holdup was correlated, with e = 2.0(NaNFr)O.6NRe 0.1 (Di/DT)2.5 , for an air-water mixture. The (Di/DT) used in this work ranged from 0.36 to 0.53